Pengembangan Customer Relationship Pada Penggunaan Jasa Air Freighter DHL Global Forwarding Semasa Pandemi COVID-19 - Immanuel Zai; Cerina; Tohmeng; Laurentcia Longli; Sweet Chen; Vina Kristini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
DHL Global Forwarding is one of the companies engaged in international logistics that is well known to many people and is one of the most widely used forwarding companies by other companies. Due to the Covid-19 pandemic, shipping companies have skyrocketed because all orders are made through the online system. The type of research conducted at the DHL Global Forwarding company uses secondary data which can be seen directly through the company's website. In the current technological era, logistics companies become a supporter in the CRM process assisted by e-commerce that makes it easier for consumers to access it.